Laboratory safety evaluation of bedinvetmab, a canine anti-nerve growth factor monoclonal antibody, in dogs. (October 2021) - Krautmann, M.; Walters, R.; Cole, P.; Tena, J.; Bergeron, L.M.; Messamore, J.; Mwangi, D.; Rai, S.; Dominowski, P.; Saad, K.; Zhu, Y.; Guillot, M.; et al.
Highlights: Bedinvetmab, a native canine anti-NGF monoclonal antibody, was well tolerated in dogs. No effects in long bone joints or immune morphology/function with bedinvetmab. No effects from short-term concurrent use of nonsteroidal anti-inflammatory drugs. Anti-drug antibodies to bedinvetmab were not detected. Abstract: Nerve growth factor (NGF), a critical mediator of nociception, is a novel analgesic therapeutic target. Bedinvetmab, a canine monoclonal antibody (mAb), binds NGF and inhibits its interaction with tropomyosin receptor kinase A (trkA) and p75 neurotrophin receptor (p75 NTR ) receptors. The objective of three integrated laboratory studies was to demonstrate the safety of bedinvetmab in adult laboratory Beagle dogs. Daily health, veterinary, clinical pathology, systemic exposure, and anti-drug antibody evaluations were performed. Study 1 additionally included electrocardiography, neurologic, and ophthalmic assessments, and radiographic monitoring of joints of the appendicular skeleton. Study 2 evaluated T-lymphocyte-dependent immune function. Study 3 evaluated the safety of short-term concurrent administration of carprofen, a nonsteroidal anti-inflammatory drug (NSAID), with bedinvetmab. Studies 1 and 3 included terminal pathology and histopathology evaluations. Study designs and procedures included directed complementary morphologic and functional evaluations of a literature- and in vitro-based list of potential safety issues related to the NGF signaling pathway and characteristics engineered into this mAb. Screening-level general procedures evaluated effects associated with mAbs that target and inhibit soluble agonist cytokines. There were no treatment-related adverse changes in clinical evaluations, clinical neurological and ophthalmic examinations, joints, immune morphology or function, and no effects of short-term concurrent NSAID usage. Treatment-emergent immunogenicity was not observed. Bedinvetmab (1 mg/kg SC monthly; 3× and 10× dose multiples) was well tolerated in normal laboratory Beagle dogs for 6 months and with 2 weeks' concurrent NSAID administration.